Understanding Liver Toxicity Induced by Polybrominated Diphenyl Ethers in Human Hepatocytes - Ramoju, Siva P. (Université d'Ottawa / University of Ottawa, 2012)
Poly Brominated Diphenyl Ethers (PBDEs) are known flame retardants with highly persistent and lipophilic in nature. The continued usage of PBDE in various products amplifies the human burden of PBDEs. It is therefore, important to study the potential toxicological and/or biological effects of PBDE exposure in human. In this study we investigated the mode of action of PBDE induced toxicity in human liver by exposing human hepatocarcinoma cells in a time (24-72h) and dose (0-100μM) dependent manner. The highest test dose caused an inhibition in cell viability up to 50% after 72h, whereas lower doses (<50μM) showed slight increase in cell viability. Likewise, higher doses caused significant accumulation of intracellular ROS over time. Further, increase in caspase-3 enzyme levels and DNA fragmentation showed that, lower brominated PBDEs induce liver toxicity through accumulation of toxic metabolites and reactive oxygen species over time leading to caspase-mediated apoptotic cell death.
Keywords: Poly Brominated Dipheny Ethers; PBDE; HepG2; Flame Retardants; DE-71; Apoptosis; Cell Viability; Oxidative Stress; Caspase-3